2019
DOI: 10.1002/lary.27909
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the establishment of primary porcine vocal fold epithelial cell cultures

Abstract: Objective: A current lack of methods for epithelial cell culture significantly hinders our understanding of the role of the epithelial and mucus barriers in vocal fold health and disease. Our first objective was to establish reproducible techniques for the isolation and culture of primary porcine vocal fold epithelial cells. Our second objective was to evaluate the functional significance of cell cultures using an in vitro exposure to an inflammatory cytokine. Methods: Epithelial cells were isolated from por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…To date, limited primary culture of VF epithelial cells has been reported from porcine VF tissue and humans. 18,19 Immortalization of epithelial cells from various human tissues (subglottis, posterior commissure, and ventricles) that are in close proximity to and surround the true membranous VF have also been described. 20 In each of these aforementioned immortalizations, the type of human epithelial cells immortalized were pseudostratified ciliated epithelium which differs from the stratified squamous epithelium from the free edge of the true membranous VF.…”
Section: Discussionmentioning
confidence: 99%
“…To date, limited primary culture of VF epithelial cells has been reported from porcine VF tissue and humans. 18,19 Immortalization of epithelial cells from various human tissues (subglottis, posterior commissure, and ventricles) that are in close proximity to and surround the true membranous VF have also been described. 20 In each of these aforementioned immortalizations, the type of human epithelial cells immortalized were pseudostratified ciliated epithelium which differs from the stratified squamous epithelium from the free edge of the true membranous VF.…”
Section: Discussionmentioning
confidence: 99%
“…Present in vitro epithelial models rely on the use of a murine fibroblast feeder layer (3T3 J2) 17 and/or a culture medium containing animal products such as foetal bovine serum (FBS) 18 , bovine pituitary extract (BPE) and cholera toxin 19 . There is a commercially available epithelial advanced therapy medicinal product (ATMP) 20 created using a 3T3-J2 feeder layer from a GMP-certified master cell bank 21 , which is exclusive to the company and would be very expensive to create independently 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Buccal mucosa has been used as a source of non-keratinised squamous epithelial cells, either as a graft 28 , 29 or as a tissue engineered product 30 . Various methods for procurement and culture of mucosal cells, such as outgrowth 31 or enzymatic digestion 18 , use of feeder layers 32 or tissue culture plastic coatings 19 and various media 33 have been reported. Green and Rheinwald initially cultured keratinocytes on growth-arrested 3T3 J2 17 , which have been shown to also promote the growth of oral epithelial cells 34 .…”
Section: Introductionmentioning
confidence: 99%
“…However, these cell culture models do not allow for the independent investigation of the vocal fold epithelium in isolation, which is of equal importance in elucidating the vocal fold tissue response to acute and chronic injury. A lone study by Erickson-DiRenzo et al [2019] demonstrated effective culture of porcine vocal fold epithelium using collagen IV, although the choice to use collagen IV was not discussed. The challenge of the DOI: 10.1159/000514200 current study lies in creating an environment suitable for rabbit vocal fold epithelial growth in the absence of fibroblasts, and to further quantify the relative contributions of each basement membrane component in the establishment and maintenance of a healthy and intact epithelial barrier.…”
Section: Introductionmentioning
confidence: 99%
“…In the development of a cell culture protocol to investigate normal and pathologic mechanisms, it is important to consider the individual components of the basement membrane, and identify which of these components (e.g., collagen I, laminin, collagen IV, or fibronectin) will provide the best translation from in vitro to in vivo. Erickson-DiRenzo et al [2019] sought to establish an isolated primary epithelial vocal fold culture method derived from porcine larynges, and demonstrated successful cultures with normative epithelial morphology and protein markers and minimal fibroblast contamination using a collagen IV protein-substrate, supporting further investigation into in vitro substrates for the support of vocal fold epithelial cell proliferation. No other studies to date have investigated the interaction between substrate and epithelium, although many have acknowledged the likelihood of this interaction playing a critical role in tissue integrity and homeostasis in other tissue types [Frisch and Francis, 1994;Suzuki et al, 2003;Coraux et al, 2008].…”
Section: Introductionmentioning
confidence: 99%